ChemInform Abstract: Synthesis of 3, 4, 5‐Trimethoxybenzene Derivatives with Substituted Triazole Group by Huisgen 1, 3‐Cycloaddition and Their Inhibitory Effects on 3T3‐L1 Adipocyte Differentiation. Issue 51 (5th December 2016) - Park, Sangkyu; Oh, Sangtae; Kim, Taejung; Ham, Jungyeob; Lee, Seokjoon
Abstract: Triazole derivatives are synthesized by Huisgen 1, 3‐cycloaddition of aromatic azides with various alkynes.